Relationship between serum LDH levels and diabetic peripheral neuropathy in type 2 diabetic patients - Sun, Meng; Wang, Zhaodi; Yan, Xu; Shen, Hangyu; Yang, Hongqiao; Qi, Yuxia; Gao, Xiang; Huang, Yi; Sun, Jie (Frontiers in Endocrinology, 2025)
BackgroundDiabetic peripheral neuropathy (DPN) is commonly observed as a long-term complication in patients with type 2 diabetes mellitus (T2DM). Recent evidence suggests that metabolic disturbances and chronic inflammation may contribute to its development. Lactate dehydrogenase (LDH), a key enzyme in glycolysis, may reflect underlying metabolic stress and inflammation, but its association with DPN remains unclear.MethodsIn this cross-sectional study, 2,060 patients with T2DM were analyzed to explore the relationship between serum LDH levels and DPN. Logistic regression and restricted cubic spline (RCS) models were used to assess linear and non-linear associations. Participants were also stratified by age, sex, hypertension, and HbA1c levels for subgroup analyses.ResultsAmong the study population, 724 (35.1%) had DPN. Higher LDH levels were independently associated with an increased risk of DPN after adjusting for potential confounders (adjusted OR per 1 U/L increase: 1.00; 95% CI: 1.00–1.01; P = 0.01). RCS analysis showed a non-linear relationship, with a threshold at 142 U/L. Participants with LDH >142 U/L had significantly higher odds of DPN (adjusted OR: 1.21; 95% CI: 1.02–1.48; P = 0.033). This association was consistent across subgroups.ConclusionSerum LDH levels are significantly and non-linearly associated with DPN in individuals with T2DM. LDH may serve as a simple and cost-effective biomarker for identifying patients at elevated risk of neuropathy, warranting further prospective validation.